2017
DOI: 10.1371/journal.pone.0179079
|View full text |Cite
|
Sign up to set email alerts
|

Biochar particle size, shape, and porosity act together to influence soil water properties

Abstract: Many studies report that, under some circumstances, amending soil with biochar can improve field capacity and plant-available water. However, little is known about the mechanisms that control these improvements, making it challenging to predict when biochar will improve soil water properties. To develop a conceptual model explaining biochar’s effects on soil hydrologic processes, we conducted a series of well constrained laboratory experiments using a sand matrix to test the effects of biochar particle size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(232 citation statements)
references
References 43 publications
(69 reference statements)
11
219
0
2
Order By: Relevance
“…The total pore volume of the mixture increased with increase in biochar fractions, as indicated by the higher water content at saturation (Table ). The result is consistent with the results of previous studies (Abel et al, ; Blanco‐Canqui, ; Liu, Dugan, Masiello, & Gonnermann, ; Omondi et al, ; Ulyett, Sakrabani, Kibblewhite, & Hann, ). The increase in pore volume is mainly attributed to the increase in macroporosity caused by the dilution effect of adding larger diameter and low‐density biochar amendment to sand (Herath, Camps‐Arbestain, & Hedley, ; Lim et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The total pore volume of the mixture increased with increase in biochar fractions, as indicated by the higher water content at saturation (Table ). The result is consistent with the results of previous studies (Abel et al, ; Blanco‐Canqui, ; Liu, Dugan, Masiello, & Gonnermann, ; Omondi et al, ; Ulyett, Sakrabani, Kibblewhite, & Hann, ). The increase in pore volume is mainly attributed to the increase in macroporosity caused by the dilution effect of adding larger diameter and low‐density biochar amendment to sand (Herath, Camps‐Arbestain, & Hedley, ; Lim et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The control sand and 5% unsieved biochar treatment showed only a small difference in saturated and residual soil moisture content, indicating 5% unsieved biochar is not sufficient to improve water retention. We attributed the increase in water retention to the presence of interparticle and intraparticle pores of the added biochar particles and their effect in altering the pore‐size distribution of amended sand (Liu et al, ). The creation of large macropores in the soil surrounding the biochar particles could increase total porosity of biochar‐amended soil (Hardie, Clothier, Bound, Oliver, & Close, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that biochar particle size, shape, and porosity act together to influence soil water properties (Liu et al 2017). Therefore, our observation here indicated that the ozone treatment may have certain relatively minor effects on these physical and morphological properties in relation to the water-retention field capacity.…”
Section: Water-retention Field Capacitymentioning
confidence: 51%
“…To assess the time‐dependent release of P from the rice husk biochar, the RH 700 material was reduced to smaller minimum dimension (0.5–1 mm) using a sieve and extracted using unbuffered DI water. This reflects biochar that has been physically fragmented through exposure to physical, biological, and chemical processes (Liu et al, 2017). A nonionic surfactant, 2‐octanol (98% for synthesis, Merck) was included, to address any short‐term effects of hydrophobicity that rapidly diminish in soil, and consequently to reflect long‐term P leaching conditions (Ojeda et al, 2015).…”
Section: Methodsmentioning
confidence: 99%